The Challenge of Counseling Research in Developing a Signature Pedagogy for Quantitative Methods - Richard S. Balkin (Teaching and Supervision in Counseling, 2020)
Research in counseling is at risk of becoming impertinent, if not irrelevant, with an over-emphasis on perceptions of counselors or counselors in-training, and a lack of evidence supporting client-centered outcomes and community needs. Students seeking doctoral degrees in training may have limited interest in research, and research courses are typically taught outside of the discipline by individuals unaffiliated with the counseling profession. Research courses may not be aligned with the needs of counseling researchers who focus on individuals and small groups. Developing a signature pedagogy emphasizing tools and methods consistent with the needs of emerging counseling researchers may be important to elevating counseling research and expanding outreach opportunities to communities, agencies and stakeholders.
Keywords: pedagogy; counseling research; efficacy; training; education